A model specification test - Knut Bartels (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
A general model specification test of a parametric model against a nonparametric or semiparametric alternative is studied. The test statistic employs a fixed kernel, not varying by a bandwidth. This test is proved to be consistent, the asymptotic distribution is derived and shown to be approximated by a bootstrap procedure.
urn:nbn:de:kobv:11-10060806
Keywords: 330; bootstrap; nonlinear regression; Model specification test; nonparametric or semiparametric alternative